First International Workshop on Bidirectional Transformations (BX 2012): Preface - Hermann, Frank; Voigtländer, Janis (Electronic Communications of the EASST, 2012)
Bidirectional transformations (bx) are a mechanism for maintaining the consistency of two (or perhaps more) related sources of information. Such sources can be databases, software models, documents, or their abstract models like graphs or trees. BX are an emerging topic in a wide range of research areas with prominent presence at top conferences in different fields. The methodologies used for bx range from classical program transformation to graph transformation techniques, from ad-hoc techniques for data synchronization to the development of domain-specific languages and their integration. The First International Workshop on Bidirectional Transformations (BX 2012) established a dedicated venue for bx in all relevant areas. It was initiated by the participants of the Dagstuhl Seminar "Bidirectional Transformations" (bx) in Germany 2011, which continued the GRACE International Meeting on Bidirectional Transformations held in Japan 2008. The workshop BX 2012 took place at the Tallinn University of Technology, Estonia on the 25th of March 2012, as a satellite event of ETAPS 2012, the European Joint Conferences on Theory and Practice of Software.